An Effective Approach to Improving Day-Case Rates following Laparoscopic Cholecystectomy. (22nd March 2011) - Clarke, M. G.; Wheatley, T.; Hill, M.; Werrett, G.; Sanders, G.
Abstract : Background . Day-case laparoscopic cholecystectomy (LC) is a safe and cost-effective treatment for gallstones. In 2006, our institution recorded an 86% laparoscopic, 10% day-case, and 5% readmission rate. A gallbladder pathway was therefore introduced in 2007 with the aim of increasing daycase rates. Methods . Patients with symptomatic gallstones, proven on ultrasound, were referred to a specialist-led clinic. Those suitable for surgery were consented, preassessed, and provided with a choice of dates. All defaulted to day case unless deemed unsuitable due to comorbidity or social factors. Results . The number of cholecystectomies increased from 464 in 2006 to 578 in 2008. Day-case rates in 2006, 2007, 2008, and June 2009 were 10%, 20%, 30%, and 61%, respectively. Laparoscopic and readmission rates remained unchanged. Conversion rates for elective cholecystectomy fell from 6% in 2006 to 3% in 2009. Conclusions . Development of a gallbladder pathway increased day-case rates sixfold without an associated increase in conversion or readmission rates.